Rancang Bangun Website Profil Sekolah sebagai Media Informasi dan Publikasi pada MTS Hubbul Wathan: Design and Construction of a School Profile Website as an Information and Publication Media at MTS Hubbul Wathan - Muh Khalladun Attamimi; Alfiah Fajriani; Zila Razilu (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to design and develop a school profile website as an official information and publication platform for MTs Hubbul Wathan. The website was developed to address the limitations of conventional information-dissemination methods still used by the school, such as bulletin boards and direct communication, which are considered ineffective, fail to reach a wide audience, and cannot provide information quickly and accurately. This study uses the Waterfall software development model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The website was built using HTML, CSS, and JavaScript on the frontend, and PHP with the CodeIgniter framework and MySQL on the backend. The implementation results show that all main features, including the school profile, teacher data, facilities, activity gallery, announcements, and the online PPDB function, operate optimally. Blackbox testing verifies that each feature meets functional requirements, while security testing confirms that the website implements input validation, password encryption, and SQL Injection prevention mechanisms. In addition, the responsive interface design ensures comfortable access via mobile devices, tablets, and computers. Based on the overall test results, the website is declared suitable for use as a long-term digital information medium that can improve publication effectiveness, information transparency, and the efficiency of school administrative services. Thus, this website is expected support the digital transformation of MTs Hubbul Wathan and meet the community's needs for obtaining educational information quickly, easily, and in a modern way.